2007
DOI: 10.3748/wjg.v13.i8.1247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastric varices and results of sclerotherapy with N-butyl 2 cyanoacrylate for controlling acute gastric variceal bleeding

Abstract: AIM:To study the prevalence, predictors and control of bleeding following N-butyl 2 cyanoacrylate (NBC) sclerotherapy of gastric varix (GV). METHODS:We analyzed case records of 1436 patients with portal hypertension, who underwent endoscopy during the past five years for variceal screening or upper gastrointestinal (GI) bleeding. Fifty patients with bleeding GV underwent sclerotherapy with a mean of 2 mL NBC for control of bleeding. Outcome parameters were primary hemostasis (bleeding control within the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 26 publications
6
25
0
3
Order By: Relevance
“…Because of its excellent efficacy, N-butyl-2-cyanoacrylate is considered to be the optimal endoscopic therapy for gastric variceal bleeding [14]. Indeed, a large number of case series have demonstrated that N-butyl-2-cyanoacrylate injection successfully controlled acute gastric varices, with overall success rates ranging between 70 % to 100 % [3][4][5][6][7][8][9][10]. Radiologic transjugular intrahepatic portosystemic shunt (TIPS) placement has also been used as a therapeutic modality in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its excellent efficacy, N-butyl-2-cyanoacrylate is considered to be the optimal endoscopic therapy for gastric variceal bleeding [14]. Indeed, a large number of case series have demonstrated that N-butyl-2-cyanoacrylate injection successfully controlled acute gastric varices, with overall success rates ranging between 70 % to 100 % [3][4][5][6][7][8][9][10]. Radiologic transjugular intrahepatic portosystemic shunt (TIPS) placement has also been used as a therapeutic modality in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Soehendra et al first reported in 1986 that bleeding from gastric varices could be controlled by intravariceal injection of the tissue adhesive agent butyl cyanoacrylate [2]. Since then, several authors have used different sclerosing agents to achieve hemostasis, but N-butyl-2-cyanoacrylate (Histoacryl™) is the only promising agent, achieving primary hemostasis in 70 % to 100 % of patients, with an early rebleeding rate ranging from 0 % to 23 % [3][4][5][6][7][8][9][10]. In fact, although sclerotherapy with 5 % ethanolamine oleate, absolute ethanol or 1 % polidocanol has been reported to control bleeding in about 66 % of patients, it has a rebleeding rate of 50 % and it is more effective in patients with gastroesophageal varices than with fundal varices [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sohendra et al [10] first reported in 1986 that bleeding from GV could be controlled by sclerotherapy using the tissue adhesive agent butyl cyanoacrylate. Since then several authors have used different sclerosing agents to achieve hemostasis in bleeding gastric varices, including N-butyl-2 cyanoacrylate (histoacryl) [11,12] , 2-octyl cyanoacrylate [13] , ethanolamine oleate injection [14] , gastric variceal banding [15] , thrombin [1] and sodium tetradecyl sulfate [16] . However, N-butyl 2 cyanoacrylate (NBC) is the only promising agent.…”
Section: Introductionmentioning
confidence: 99%
“…Le risque hémorragique par rupture de varices gastriques est moins fréquent que celui de la rupture des varices oesophagiennes [2]. L'incidence du saignement est de 10-36 %, mais l'hémorragie est habituellement plus abondante et difficile à contrôler [6].…”
Section: Discussionunclassified
“…Depuis sa première description par Soehendra en 1986 [1], la sclérose endoscopique avec une colle biologique (butylcyanoacrylate) est largement utilisée dans le traitement des varices oesogastriques hémorragiques ; elle est considérée actuellement comme le traitement de choix pour l'oblitéra-tion des varices gastriques [2]. Cette technique a été associée à diverses complications transitoires : hyperthermies, dysphagies, brûlures rétrosternales [3].…”
Section: Introductionunclassified